The Discount Rate Problem in Capital Rationing Situations: Comment - Lockett, A. Geoffrey; Tomkins, Cyril (Journal of Financial and Quantitative Analysis, 1970)
Recently, Lusztig and Schwab [5] drew attention to a problem which occurs when applying linear programming methods to portfolio selection where capital is rationed over several investment periods. The problem is to determine the relevant discount rate with which to calculate the net present values of the objective function when this same rate is dependent upon the optimal solution to the linear program. Lusztig and Schwab suggested a neat procedure by which it was claimed that one could overcome this difficulty and which also does not rely upon the measurement of subjective utility as did the Baumol and Quandt approach [2]. It was decided to test the Lusztig and Schwab model (afterwards called the L-S procedure for brevity) on a hypothetical problem, and doing so resulted in two conclusions:(a) The L–S procedure, as described, is incomplete but with small modification may be useful; however, (b) concentration upon the discount rate problem in isolation from other capital budgeting problems may well be a pointless exercise.